Effectiveness of the universal prevention program 'Healthy School and Drugs': Study protocol of a randomized clustered trial - Malmberg, Monique (BioMed Central, 2010)
BACKGROUND: Substance use is highly prevalent among Dutch adolescents. The Healthy School and Drugs program is a nationally implemented school-based prevention program aimed at reducing early and excessive substance use among adolescents. Although the program's effectiveness was tested in a quasi-experimental design before, many program changes were made afterwards. The present study, therefore, aims to test the effects of this widely used, renewed universal prevention program. METHODS/DESIGN: A randomized clustered trial will be conducted among 3,784 adolescents of 23 secondary schools in The Netherlands. The trial has three conditions; two intervention conditions (i.e., e-learning and integral) and a control condition. The e-learning condition consists of three digital learning modules (i.e., about alcohol, tobacco, and marijuana) that are sequentially offered over the course of three school years (i.e., grade 1, grade 2, and grade 3). The integral condition consists of parental participation in a parental meeting on substance use, regulation of substance use, and monitoring and counseling of students' substance use at school, over and above the three digital modules. The control condition is characterized as business as usual. Participating schools were randomly assigned to either an intervention or control condition. Participants filled out a digital questionnaire at baseline and will fill out the same questionnaire three more times at follow-up measurements (8, 20, and 32 months after baseline). Outcome variables included in the questionnaire are the percentage of binge drinking (more than five drinks per occasion), the average weekly number of drinks, and the percentage of adolescents who ever drunk a glass of alcohol and the percentage of adolescents who ever smoked a cigarette or a joint respectively for tobacco and marijuana. DISCUSSION: This study protocol describes the design of a randomized clustered trial that evaluates the effectiveness of a school-based prevention program. We expect that significantly fewer adolescents will engage in early or excessive substance use behaviors in the intervention conditions compared to the control condition as a direct result of the intervention. We expect that the integral condition will yield most positive results, compared with the e-learning condition and control condition. TRIAL REGISTRATION: The protocol for this study is registered with the Nederlands Trial Register NTR1516